2015
DOI: 10.1007/8904_2015_464
|View full text |Cite
|
Sign up to set email alerts
|

SUCLA2 Deficiency: A Deafness-Dystonia Syndrome with Distinctive Metabolic Findings (Report of a New Patient and Review of the Literature)

Abstract: SUCLA2 encodes for a subunit of succinylcoenzyme A synthase, the enzyme that reversibly synthesises succinyl-coenzyme A and ATP from succinate, coenzyme A and ADP in the Krebs cycle. Disruption of SUCLA2 function can lead to mitochondrial DNA depletion. Patients with a SUCLA2 mutation present with a rare but distinctive deafness-dystonia syndrome. Additionally, they exhibit elevated levels of the characteristic biochemical markers: methylmalonate, C4-dicarboxylic carnitine and lactate are increased in both pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…To date, 51 patients have been reported with SUCLA2 deficiency [6,7,20,24,29,41,44,46,49,50,52,54], and 21 patients with SUCLG1 deficiency, due to different mutations [7]. Patients with SUCLG1 mutations may have an extremely severe phenotype with antenatal manifestations of the disorder, severe acidosis with lactic aciduria in the first day of life and death within 2–4 days [53] or a phenotype similar to those of patients with SUCLA2 mutations.…”
Section: Introductionmentioning
confidence: 99%
“…To date, 51 patients have been reported with SUCLA2 deficiency [6,7,20,24,29,41,44,46,49,50,52,54], and 21 patients with SUCLG1 deficiency, due to different mutations [7]. Patients with SUCLG1 mutations may have an extremely severe phenotype with antenatal manifestations of the disorder, severe acidosis with lactic aciduria in the first day of life and death within 2–4 days [53] or a phenotype similar to those of patients with SUCLA2 mutations.…”
Section: Introductionmentioning
confidence: 99%
“…Such finding seems to suggest that SCS A-β is critical for neuronal physiology. This has been supported by further clinical observations that mutations in SUCLA2 cause loss of SCS A-β function resulting in lethal neurological disorders including infantile Leigh or Leigh-like syndrome 5 7 . Furthermore, SUCLA2 +/− mice demonstrated pronounced brain mitochondrial dysfunction 8 .…”
Section: Introductionmentioning
confidence: 64%
“…Visual analysis of the structures (Fig. 3 ) showed that both loci fell near the protein’s “phosphate shuttle” loop [ 18 ], indicating that the replacement of the wild-type residue might interfere with the functional role of this loop. This was particularly noticeable for Gly326, which lies in close contact with residue His299 of the loop, and occurs at a packed location in the structure.…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, the mitochondrial dysfunction in deficient fibroblasts from P24 was rescued via the stable expression of the SUCLA2 protein through lentiviral transduction. This suggests that SUCLA2 is the gene likely affected in this patient, although his/her symptoms were atypical [ 18 , 38 ]. With respect to ASCF3 , individuals P24, P25, P26 and P27 were diagnosed as having isolated MMA since the urinary malonic acid that identifies CMAMMA can be easily missed [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation